2012
DOI: 10.1016/j.athoracsur.2012.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Postthoracotomy Pain and Health-Related Quality of Life

Abstract: Background Pain following thoracotomy is common. The objective of this study was to assess whether pain 3 months post-thoracotomy negatively impacts quality of life. Methods One hundred ten patients were prospectively assessed using the Short Form-36 (SF-36) Health Survey before and 3 months after elective thoracotomy. Pain and medication use were evaluated by questionnaire. Patients experiencing pain at 3 months were compared with patients who did not have post-thoracotomy pain. Results Seventy-five patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 29 publications
4
58
3
Order By: Relevance
“…Overall, the rate of neuropathic pain was rather low in our study (26-28%) compared to previous studies with neuropathic rates reported to range between 40-50% (3,17,19). Again, studies were quite heterogeneous concerning patient characteristics and surgical approaches.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Overall, the rate of neuropathic pain was rather low in our study (26-28%) compared to previous studies with neuropathic rates reported to range between 40-50% (3,17,19). Again, studies were quite heterogeneous concerning patient characteristics and surgical approaches.…”
Section: Discussioncontrasting
confidence: 47%
“…In this regard the international association for the study of pain defines Post Thoracotomy Pain Syndrome (PTPS) as a pain that recurs or persists along a thoracotomy incision at least two months following the surgical procedure (2). Of note PTPS is a very common condition following thoracotomy with incidence rates reportedly ranging between 30% and 50% (3)(4)(5). In addition PTPS is mainly attributed to neuropathic pain (6).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment is generally conservative because it does not cause disability and limitations in daily life activities in the vast majority of patients. Only 5% of patients develop severe pain and disability-related difficulties in daily living activities [1,4,5,11]. One study reported that 27% of patients described chronic pain at 6 months post-thoracotomy and 8.2% had pain at a level that limited their daily activities [12].…”
Section: Introductionmentioning
confidence: 99%
“…Patients who experience post-thoracotomy pain at 3 months are at greatest risk for significantly decreased physical functioning and vitality [9]. A recent systemic review of literature pointed the evidence in favor of thoracic paravertebral block or thoracic epidural analgesia as the first-choice therapies for post-thoracotomy analgesia [10].…”
Section: Thoracic Paravertebral Blocks For Thoracic Surgerymentioning
confidence: 99%
“…Minimally invasive cardiac surgery through thoracotomy also carries increased risk of severe post-thoracotomy pain syndrome compared with median sternotomy [14] Again, the primary factor that might influence post-thoracotomy pain is the severity of pain in the immediate postoperative period. Thus, inadequately controlled pain can increase postoperative morbidity, as well as reduce quality of life and patient satisfaction [9].…”
Section: Thoracic Paravertebral Blocks For Minimally Invasive Cardiacmentioning
confidence: 99%